In vivo noninvasive microscopy of human leucocytes. Issue 1 (December 2017) - Winer, Matan; Zeidan, Adel; Yeheskely-Hayon, Daniella; Golan, Lior; Minai, Limor; Dann, Eldad; Yelin, Dvir
Abstract Leucocytes play a key role in our immune system, protecting the body against infections using a wide range of biological mechanisms. Effective imaging and identification of leucocytes within the blood stream in patients is challenging, however, because of their low volume fraction in the blood, the high tissue scattering and the rapid blood flow. Spectrally encoded flow cytometry (SEFC) has recently been demonstrated effective for label-free high-resolutionin vivo imaging of blood cells using an optical probe that does not require mechanical scanning. Here, we use SEFC to noninvasively image leucocytes at different imaging depths within small vessels in human volunteers, and identify visual differences in cell brightness and nuclei shapes, that would help distinguish between the two most abundant leucocyte types. The observed differences match thein vitro characteristics of isolated granulocytes and mononuclear cells. The results prove the potential of the system for conducting differential leucocyte count and as an effective research tool for studying the function and distribution of leucocytes in humans.